Advances in Pediatric Research 2019
DOI: 10.35248/2385-4529.19.6.31
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the 4-Digit Code, Canadian 2015, Australian 2016 and Hoyme 2016 fetal alcohol spectrum disorder diagnostic guidelines

Abstract: Background: As clinicians strive to achieve consensus worldwide on how best to diagnose fetal alcohol spectrum disorders (FASD), the most recent FASD diagnostic systems show convergence and divergence. Applying these systems to a single clinical population illustrates the contrasts between them, but validation studies are ultimately required to identify the best system. Methods: The 4-Digit-Code, Hoyme 2016, Canadian 2015 and Australian 2016 FASD diagnostic systems were applied to 1,392 patient records evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 26 publications
2
28
0
Order By: Relevance
“…Since FASD first appeared in the literature, various diagnostic labels and criteria have been proposed, implemented, and updated (e.g., Benz et al, 2009; Cook et al, 2016; World Health Organization, 2005). Research has shown that evaluating the same individual using different diagnostic systems can result in conflicting diagnostic outcomes, both in terms of the specific label applied (e.g., FAS vs. ARND), as well as whether or not a PAE‐related diagnosis should be made (Astley Hemingway et al, 2019; Coles et al, 2016). Regarding the present review, many of the included studies relied on a previous diagnosis of FASD as their reference standard, with no information regarding which guidelines were followed to make the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since FASD first appeared in the literature, various diagnostic labels and criteria have been proposed, implemented, and updated (e.g., Benz et al, 2009; Cook et al, 2016; World Health Organization, 2005). Research has shown that evaluating the same individual using different diagnostic systems can result in conflicting diagnostic outcomes, both in terms of the specific label applied (e.g., FAS vs. ARND), as well as whether or not a PAE‐related diagnosis should be made (Astley Hemingway et al, 2019; Coles et al, 2016). Regarding the present review, many of the included studies relied on a previous diagnosis of FASD as their reference standard, with no information regarding which guidelines were followed to make the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…These include the relatively “hidden” nature of the disorder, with a large proportion of those with FASD presenting with no overt outward physical signs (~90%), as well as underreporting of alcohol use during pregnancy due to substantial stigma and fear of repercussions (Astley, 2010; Corrigan et al, 2019). Additional barriers include a continued lack of system‐level resources, complex and variable clinical presentations, and limited FASD knowledge and awareness among professionals needed to effectively recognize, assess, and provide support to individuals with FASD and their families (Astley Hemingway et al, 2019; Corrigan et al, 2019; McLachlan et al, 2020; Wedding et al, 2007). Guidelines for diagnosing FASD also range considerably across countries with respect to criteria and diagnostic nosology, which continue to change over time (see Coles et al, 2016, for a review).…”
Section: Introductionmentioning
confidence: 99%
“…Pediatricians and psychologists trained and with experience in FASD clinical diagnostic guidelines performed the assessments using the Institute of Medicine validated diagnostic criteria updated by Hoyme et al [ 6 ] and matched to other validated criteria [ 7 , 19 , 28 , 29 ]. The diagnosis was based on a specific clinical assessment and on various cognitive and behavioral standardized neuropsychological tests (Wechsler Intelligence Scale for Children (WISC), Wechsler Adult Intelligence Scale (WAIS), A Developmental NEuroPSYchological Assessment (NEPSY-II), Rey-Osterrieth complex figure, Evaluation of Reading Processes for Secondary Education Students (PROLEC-SE), Child Behavior Checklist (CBCL) and Vineland (VABS-II)), with unified criteria and previous uniform formal training for the professionals from the 3 clinical units [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…87 158 Sentinel facial features Clinical assessment of facial features will be completed via direct measurement (where possible) and/or assessed from a photograph, analysed using the University of Washington facial analysis software. 159 Smooth philtrum and thin upper lip will be assessed using the University of Washington Caucasian or African American (depending on what is individually appropriate) lip-philtrum guide (1 or 2), where a rank of 4 or 5 meets criteria for FASD sentinel facial features. The Scandinavian (Stromland) chart will be utilised to measure palpebral fissure length where a result of >2 SD below the mean (<3rd percentile) is significant.…”
Section: Assessment Of Paementioning
confidence: 99%